PKM Leksem “ALLAH” Tanpa Bergaya Bahasa Personifikasi Kepada Jemaah Solat Mesjid Al Hikmah Kecamatan Medan Tembung - Ahmad Laut Hasiibuan; Rosmawati Harahap; Rahmat Kartolo; Effendi Barus (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2024)
Socialization activities related to the urgency of how to speak well in conveying Islamic material well without hurting feelings or offending other religions is something very basic. The aims of PKM are (1) to increase understanding of how to speak in Islamic da'wah communication, (2) to improve understanding of the concept of Allah as Rabb for participants. The method used in socializing the lexeme "Allah" without personified language to the congregation of the Al Hikmah Mosque. prayers Medan Tembung District is lecture and discussion. Providing lectures and discussions in the implementation of this service is based on the theory of media discourse analysis by paying attention to how it should be: conveying Islamic da'wah orally regarding the lexeme Allah/Rabb, not offending other people in speaking, and speaking management as a strategy so that mosque congregants become more enthusiastic when listening to the preaching. Islam. .The results obtained in this PKM are increased understanding of how to speak in Islamic da'wah communication, (2) improved understanding of the concept of Allah as Rabb by service participants. With the implementation of this PKM, the presentation of rhetoric related to the lexeme Allah as da'wah material is more developed and interesting, and makes it easier for the audience to accept the objectives of the da'wah regarding the concept of the lexeme Allah/Rabb based on the meaning of the words in the Al-Quran Surah Al Ikhlas.